INFLUENCE OF NANO ZINC OXIDE ON THE IN VITRO CALLUS GROWTH, EX VITRO TUBER YIELD AND NUTRIONAL QUALITY OF POTATO (Solanum tuberosum L.) CULTIVARS UNDER SALT STRESS - E. S. Alghamdi; M. Farooq; E.M.R. Metwali (Journal of Animal and Plant Sciences, 2022)
Potato (Solanum tuberosum L.) is one of the leading vegetable crops around the world. However, its growth, yield, and quality are reduced by several abiotic stresses such as salt stress. This study, consisted of two independent experiments was conducted to examine the effects of salt stress in potato and influence of nanoparticle-sized zinc (ZnO-NPs) in improving salt tolerance. The first experiment was conducted under in vitro conditions to evaluate the regenerated callus growth in response to the presence or absence of ZnO-NPs under different levels of NaCl (0, 17, 34, 51 and 68 mM). The second experiment was conducted using in vitro derived plantlets treated ex vitro with ZnO-NPs to evaluate its effect on tuber yield and nutritional quality under salt stress (0.0, 1.0, 2.0, 3.0 and 4.0 g L-1). In both experiments, ZnO-NPs were applied at 0.0 or 50 mg L-1 to three potatoes cvs. Spunta, Nicola, and Hermes raised under five levels of NaCl-induced salt stress: 0, 17, 34, 51 and 68 mM. Salt stress significantly reduced the in vitro callus growth progressively with increasing NaCl levels, while ZnO-NPs had a positive impact on growth under salt stress. Potato tubers harvested ex vitro differed significantly for calcium and iron under different levels of salt stress in response to ZnO-NPs application. The number of tubers responded negatively to increasing levels of NaCl with or without ZnO-NPs application. All three potato cultivars, grown under 34 mM NaCl, regardless of ZnO-NPs application, had a significantly higher number of tubers than when grown at other NaCl concentrations. The highest number of tubers was recorded for all three tested potato cultivars receiving ZnO-NPs under non-saline conditions, whereas the lowest number was recorded in plants under high levels of salinity, with or without ZnO-NPs. The cv. Spunta was the least affected by salt stress followed by the cv. Hermis and cv. Nicola for most traits. Application of ZnO-NPs proved effective in ameliorating the salinity-induced harmful effects on yield and quality of potato.
Keywords: Potato; nanoparticles; NaCl; meristem culture; calcium; iron; protein